2018
DOI: 10.7589/2017-09-239
|View full text |Cite
|
Sign up to set email alerts
|

TICK VECTOR AND DISEASE PATHOGEN SURVEILLANCE OF NILGAI ANTELOPE (BOSELAPHUS TRAGOCAMELUS) IN SOUTHEASTERN TEXAS, USA

Abstract: Nilgai ( Boselaphus tragocamelus) are nonnative bovines that were originally introduced as game animals to one large, south Texas, US ranch but that are now present throughout southeastern Texas from Baffin Bay to Harlingen and in northern Mexico at least as far west as Durango. Between October 2014 and January 2017, nilgai ( n=517) were examined for the presence of tick ectoparasites, with particular interest in the cattle fever tick, Rhipicephalus ( Boophilus) microplus. These animals were either hunter kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Over the last four decades, ungulate wildlife such as WTD and nilgai have adversely affected success of the CFTEP [ 7 , 10 , 19 ]. In 2010, the need to refine current SCFT tick models to include SCFT host interactions was identified as a key research goal for success of the eradication programme [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last four decades, ungulate wildlife such as WTD and nilgai have adversely affected success of the CFTEP [ 7 , 10 , 19 ]. In 2010, the need to refine current SCFT tick models to include SCFT host interactions was identified as a key research goal for success of the eradication programme [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currie [ 39 ] reported an average infestation of 13 adult SCFT per WTD in south Texas (Zapata County). Olafson et al [ 19 ] reported a mean of 5.4 SCFT per nilgai in south Texas (Cameron and Willacy counties). The relative metabolic body size and agility of nilgai indicate they are as ill-equipped as cattle to remove ticks by grooming, suggesting that 5.4 may be at the low end of probable per capita tick loads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…populations, but they did not find evidence of deer being able to allow either B. bovis or B. bigemina to complete their transmission cycles. It was further studies by Ueti and collaborators [ 29 ] that confirmed that deer cannot be infected with virulent B. bovis isolates.…”
Section: Epidemiology and Diagnostic Tools For The Detection And Cmentioning
confidence: 98%
“…For example, a knowledge gap exists on CFT infestation and the circulation of Babesia pathogens in wildlife and the actual infection rate in Mexican cattle. These aspects are of grave concern for the U.S. [ 29 , 30 ]. In particular, participants in the meeting were most interested in understanding the ecology of R. microplus and R. annulatus in the Texas–Mexico transboundary region, as well as how white-tailed deer, Odocoileus virginianus (Zimmerman) and nilgai, Boselaphus tragocamelus (Pallas) complicate CFT and hemoparasite management efforts.…”
Section: Epidemiology and Diagnostic Tools For The Detection And Cmentioning
confidence: 99%